2012
DOI: 10.1002/jbmr.1751
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of anoctamin-6/Tmem16f, a regulator of phosphatidylserine scrambling in osteoblasts, leads to decreased mineral deposition in skeletal tissues

Abstract: During vertebrate skeletal development, osteoblasts produce a mineralized bone matrix by deposition of hydroxyapatite crystals in the extracellular matrix. Anoctamin6/Tmem16F (Ano6) belongs to a conserved family of transmembrane proteins with chloride channel properties. In addition, Ano6 has been linked to phosphatidylserine (PS) scrambling in the plasma membrane. During skeletogenesis, Ano6 mRNA is expressed in differentiating and mature osteoblasts. Deletion of Ano6 in mice results in reduced skeleton size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 74 publications
4
106
1
2
Order By: Relevance
“…These results suggest that, under physiological conditions, TMEM16F plays an important role in microparticle shedding. TMEM16F dependency has been similarly observed during bone tissue mineralization (39), during which PtdSer-rich matrix vesicles containing concentrated phosphate and Ca 2+ ions bud off from the plasma membranes (40). Our EM images revealed that the rod-like extensions that formed on the surface of the activated platelets were released in a TMEM16F-dependent manner, consistent with the possibility that microparticle release from the activated platelets is associated with morphological changes.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that, under physiological conditions, TMEM16F plays an important role in microparticle shedding. TMEM16F dependency has been similarly observed during bone tissue mineralization (39), during which PtdSer-rich matrix vesicles containing concentrated phosphate and Ca 2+ ions bud off from the plasma membranes (40). Our EM images revealed that the rod-like extensions that formed on the surface of the activated platelets were released in a TMEM16F-dependent manner, consistent with the possibility that microparticle release from the activated platelets is associated with morphological changes.…”
Section: Discussionsupporting
confidence: 82%
“…However, of the five TMEM family members (16C, 16D, 16F, 16G, and 16J) that can scramble lipids, only 16F is expressed in muscle, lymphocytes, and bone marrow. In fact, Ehlen et al recently showed that TMEM16F Ϫ/Ϫ osteoblasts lost the ability to scramble PS, leading to the decreased deposition of mineral in the bone tissues (57). It will be interesting to examine whether the other tissues such as muscles and immune system develop normally in TMEM16F Ϫ/Ϫ mice or in patients with Scott syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…During vertebrate skeletal development, specialized cells, the osteoblasts, produce a mineralized bone matrix by deposition of hydroxyapatite crystals in the extracellular collagen matrix, where they become embedded and differentiate into osteocytes (1)(2)(3). This process requires the organized transport of high concentrations of Ca 2ϩ and phosphate ions into the extracellular matrix without inducing premature crystallization.…”
Section: Ncx1mentioning
confidence: 99%